PROCESS OF ACCEPTANCE AND NURTURING BY PARENTS TO MAINTAIN CARING AFFECTION TO THE CHILDREN WITH HYDROCEPHALUS - Sri Ageng Wirdhana; Agus Naryoso, S.Sos, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Based on data from The Ministry of Health Republic of Indonesia, there were 20 newborn babies suffered hydrocephalus from every 10.000 birth in Indonesia, Margaretha (Clinical Pshychology and Mental Health, 2014: Vol. 03, No.2). Hydrocephalus is a condition when the main characteristic is the excessive liquid accumulation in brain. This research aim to explain the process of acceptance and nurturing by parents to maintain caring affection to hydrocephalus children. This research used descriptive qualitative approach with interpretive paradigm to interpret and understand attitude. This research used fenomenology approach, Self Acceptance Theory, Symbolic Interactionism Theory, Verbal Nonverbal Theory, and The Emotion of Communication Theory. Research was conducted to three informants, with differentiations, parents who have children that still suffering hydrocephalus, parents who have hydrocephalus children in recovery process/therapy, and parents who have children that already healed from hydrocephalus disease. The result of this research is that not every parents who have hydrocephalus children directly accepted it.When the children just born, parents did not believe in it condition, they wanted to scream, cried (informant III), did not want to nurture the children well, and ignored the children without gave any attention (informant I). Nevertheless, many peoples such as family and neighbour gave support to them and made parents surely strong enough to accept the condition of the children who sick and can looked after their children as well. Communication activities that be done by parents towards hydrocephalus children through verbal and nonverbal communication is very important and be needed in nurturing children with hydrocephalus disease, such as caress, carry, kiss, walking around, using affection words, beside doing spiritual communication like reading Al Qur’an and reading shalawat that will cure hydrocephalus children. Those kind of activities make the children feel comfort and joy when be given affection by their parents. That was nonmedical therapy from parents to heal their children who suffer hydrocephalus beside from medical treatment. This research also found that among three childrens who suffer hydrocephalus, one of them can totally healed. Beside medical treatment, parents nurturing with fully affection also be needed.